Monetary Transmission through Rural Banks on Economic Development - Sipahutar, Mangasa Augustinus; Surya, Tarida Marlyn (Jurnal Ekonomi dan Studi Pembangunan, 2018)
ABSTRACTRural Banks (BPRs) is the transmission channel of monetary policy to the real sectors of the economy, especially on the scale of Micro, Small and Medium Enterprises (MSMEs). Although commercial banks also allocate credits to the MSMEs sector, however, the presence of BPRs that specifically perform banking activities in the MSMEs sector can be a benchmark for measuring the viability of monetary transmission into the MSMEs sector.Â  This study aims to measure the role of BPRs in monetary transmission to MSMEs sector, especially in Municipality and District of Bogor that geographically bordering directly. Determination of these two areas is intended to understand the credit depth of BPRs in relation to regional economic growth and the results are expected to avoid economic disparity in both regions. This study used VECM model to measure the causality between credit depth and economic growth, and OLS to measure the relationship between poverty to unemployment and credit depth. The VECM model showed uncertainty of Grangers causality between credit depth and economic growth. This explains that it takes a higher credit depth of BPRs to promote economic growth. For Municipality of Bogor, changed of credit depth by 1 basis point can reduce poverty by 3.51 basis points, and changed in unemployment by 1 basis point will change poverty in the same direction by 0.09 basis points. Meanwhile, in District of Bogor, changed of credit depth by 1 basis point can reduce poverty by 6.95 basis points, and changed in unemployment by 1 basis point will change poverty in the same direction by 0.26 basis points.Keywords: monetary transmission, MSMEs, poverty, rural banks, unemploymentJEL Classification: E50; G21; R58